Learning without Teachers (?): a study of Herman Hesse’s Siddhartha - Bhattarai, Nitya Raj (Journal of Business and Social Sciences, 2021)
The title character in Herman Hesse’s novel, Siddhartha, tried to revolt against teacher-centered teaching and started his own journey to get enlightenment through self-quest or self-investigation. However, this research paper studies Siddhartha declaration acquiring enlightenment through his self- education with contradictory ideas and marks a direct or indirect involvement of teachers in his education. The essay supports its line of departure giving the background of Siddhartha’s journey of enlightenment, studying his self- education as a part of teacher-based education by answering the question in two different topics (why did he leave teachers? / Can education be possible without teachers?) and finally draw its conclusion. Though Siddhartha is an artistic work and the ideas of this paper may not be applicable in the real classroom scenario, the reliability of the analysis of the book would become fruitful since it gives some perspectives to understand our practices philosophically- if not practically.